Cointegration, Causality and Intern Portfolio Diversification: An Investigation of Diversification Op-in the MENA Markets. - K. Kagigi , Dr. Ahmed; A. Kagigi, Dr. Khaled (Dirasat in Economics and Business, 2021)
This paper empirically examines the stock market integration and possible diversification opportunities across the MENA and the U.S. stock markets by using a sample of monthly data from 2010 to 2020. The paper investigates stock market interdependence from two perspectives which are 'long-term' and 'short-term'. For long for long-run interdependence, the cointegration approaches of Johansen (1988) and Gregory and Hansen (1996) were used. Regarding the short-run interdependence, the Granger causality test proposed by Granger (1969) has been employed. Results under both cointegration approaches indicate no evidence of long-run relationships between the MENA and the U.S. stock markets, except for the stock market of Jordan, which suggests potential benefits from investments in the MENA markets for U.S. investors. On the other hand, only Bahrain and the UAE stock markets are cointegrated within the MENA markets, indicating substantial benefits for investors wishing to diversify across the MENA markets. The Granger causality test provides evidence of no short-run relationships between the MENA stock markets and the U.S. stock market; therefore, variations in the U.S. stock index are not transmitted to the MENA stock indices and vice versa. Alternatively, Granger causality tests reveal strong evidence of short-run causal linkages among MENA stock markets. Results show unidirectional Granger causality running from the stock market of Morocco to Egypt and Jordan stock markets. Additionally, unidirectional causality was detected from Egypt and Qatar's stock markets to Bahrain and Oman stock markets, respectively.